Effectiveness of E-Module and Learning Style on Self-Regulation Learning Model to Increase the Occupational Safety and Health Knowledge for Mechanical Education Students - Nurlaela Nurlaela,; Mohd Zulfakar Mohd Nawi,; Achmad Romadin, (Journal of Technical Education and Training, 2025)
Vocational education is designed with learning that is relevant to the industrial sector. In learning activities, teaching materials are essential to support learning goals. The study aimed to identify the effectiveness of the E-module and learning style on application learning to increase the occupational safety and health knowledge for vocational education. This research is quantitative on variables bound between variables. The population of the study are all students of the education machine engineering faculty that have taken the Health and Safety course in the academic year 2023/2024. The methods used to collect the data needed in the research are R and D, which include developing instruments; lesson plans, practice questions, and quizzes; pre-test and post-test questions, learning style questionnaires, and E-module. The research results show that the E-module increases the effective health and safety work learning achievements, and with that, the style of learning lacking learning effectiveness in improving health and safety work depends on methods and the use of the E-module. Simultaneously, E-module and learning-style learning achievements effectively increase health and safety, especially for the visual learning style; the effectiveness of the E-module has a good outcome. Furthermore, the use of E-module and learning style development is needed.